Necroscope. Defilers - Lumley, Brian (London : Hodder & Stoughton, 2001)
Jake Cutter, a new Necroscope, or vampire hunter, with E-Branch, the paranormal unit of the British Secret Service, leaves the agency open to a vampire attack on the Greek island of Krassos while he pursues a personal vendetta and tries to deal with the constant whispering of the dead vampire Korath who is stuck inside his mind.
Booklist
Library Journal
Adult.
Adult
Keywords: Vampires -- Fiction; Horror fiction; Vampires -- Fiction; England -- Fiction; England -- Fiction; Horror tales